Molecular and Anatomical Signatures of Sleep Deprivation in the Mouse Brain - Thompson, Carol L.; Wisor, Jonathan P.; Lee, Chang-Kyu; Pathak, Sayan D.; Gerashchenko, Dmitry; Smith, Kimberly A.; Fischer, Shanna R.; Kuan, Chihchau L.; Sunkin, Susan M.; Ng, Lydia L.; Lau, Christopher; Hawrylycz, Mike; et al. (Frontiers in Neuroscience, 2010)
Sleep deprivation (SD) leads to a suite of cognitive and behavioral impairments, and yet the molecular consequences of SD in the brain are poorly understood. Using a systematic immediate-early gene mapping to detect neuronal activation, the consequences of SD were mapped primarily to forebrain regions. Sleep deprivation was found to both induce and suppress immediate early gene expression (and thus neuronal activity) in subregions of neocortex, striatum, and other brain regions. Laser microdissection and cDNA microarrays were used to identify the molecular consequences of SD in 7 brain regions. In situ hybridization for 222 genes selected from the microarray data and other sources confirmed that robust molecular changes were largely restricted to the forebrain. Analysis of the ISH data for 222 genes (publicly accessible at http://sleep.alleninstitute.org) provided a molecular and anatomic signature of the effects of SD on the brain. The SCN and the neocortex exhibited differential regulation of the same genes, such that in the SCN genes exhibited time-of-day effects while in the neocortex, genes exhibited only SD and W effects. In the neocortex, SD activated gene expression in areal-, layer-, and cell type-specific manner. In the forebrain, SD preferentially activated excitatory neurons, as demonstrated by double-labeling, except for striatum which consists primarily of inhibitory neurons. These data provide a characterization of the anatomical and cell-type specific signatures of SD on neuronal activity and gene expression that may account for the associated cognitive and behavioral effects.